Aportes de la implementación de la plataforma Isolucion para la mejora del SIG de la empresa Algranel S.A. (2021)
This research article aims to analyze the contribution of the implementation of the ISOLUCIÓN platform in the company ALGRANEL S.A in the GIS system; checking the optimization of procedures, the disciplined use of quality tools, communication and the management of continuous improvement in the areas within the Integrated Management System through a qualitative methodological approach with the use of questionnaires, observation, interviews and documentary review that allows to evidence phases such as the diagnosis of the company in matters of Information Management and Quality Management, later to demonstrate the advantages of the implementation of the software based on the needs of the company and finally to evidence the process implementation with the evaluation and verification of this program.